2015
DOI: 10.1111/1751-2980.12173
|View full text |Cite
|
Sign up to set email alerts
|

Continuous venovenous hemodiafiltration for hyperlactatemia caused by telbivudine in a patient with chronic hepatitis B: A case report and update review

Abstract: Although there have been reports on telbivudine-induced myopathy and creatine kinase (CK) elevation, few reports focus on its effect on hyperlactatemia in patients with chronic hepatitis B (CHB). Here we reported a case of hyperlactatemia during telbivudine treatment. A 26-year-old Chinese man had been receiving telbivudine for CHB since July 2011, with a CK level of 68 U/L before the antiviral therapy. After 3 months he felt muscular weakness in both upper and lower extremities. A check in the local clinic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Although myalgia and elevated blood CPK levels were reported in a higher number of patients in the telbivudine arm, the rates were consistent with the findings reported earlier in the literature[12,15,18,19]. It is recommended that serum CPK levels should be monitored closely during treatment with telbivudine[20]. …”
Section: Discussionsupporting
confidence: 81%
“…Although myalgia and elevated blood CPK levels were reported in a higher number of patients in the telbivudine arm, the rates were consistent with the findings reported earlier in the literature[12,15,18,19]. It is recommended that serum CPK levels should be monitored closely during treatment with telbivudine[20]. …”
Section: Discussionsupporting
confidence: 81%
“…found that a case with telbivudine-induced lactic acidosis had a history of hypokalemic periodic paralysis, but the relationship between the pre-existence of myopathy and telbivudine treatment was uncertain [ 6 ]. However, like the case of another previous study, our patient also had no heavy exercise or heavy drinking, and had no history of diabetes mellitus [ 18 ]. Thus the risk factors for telbivudine-induced lactic acidosis or MOF are still ambiguous and need to be further explored.…”
Section: Discussionmentioning
confidence: 57%
“…Wang et al . described a patient who developed hyperlactatemia during telbivudine treatment and was successfully treated with continuous venovenous hemodiafiltration [ 18 ]. However, another patient with telbivudine-induced rhabdomyolysis developed acute renal failure and metabolic acidosis by day 18 after admission and, despite hemofiltration, died within 24 hours of developing these symptoms [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dasabuvir-ombitasvir-paritaprevirritonavir (3), 36 sulfamethoxazoletrimethoprim (3), 31,37,38 telbivudine (2) 39,40 Entecavir (7), 41 linezolid (19), [21][22][23][42][43][44][45][46][47][48][49][50] ribavirin-sofosbuvir (5) 51…”
Section: Discussionunclassified